Effects of Military Service on Marital Stability Among World War II U.S. Veterans of Japanese Descent. Issue 9 (23rd June 2018) - Mackintosh, Margaret-Anne; Schaper, Kim M; Willis, Emy A; Edland, Steven; Liu, Catherine; White, Lon R
Abstract: Introduction: This study had two goals. First, we investigated how World War II (WW II) military service impacted marital stability during men's young and middle adulthood in a large community sample of American men of Japanese descent. Second, within a subgroup of WW II veterans, we assessed how the level of combat exposure affected marital stability. Material and Methods: The Honolulu Heart Program and later Honolulu-Asia Aging Project were longitudinal, community-based studies of Japanese–American men living in Hawai'i. This study is a secondary data analysis of 1, 249 male WW II veterans and 3, 489 men of Japanese descent who were civilians during WW II, born 1910–1919, who completed interviews at the first (1965–1968) and third (1971–1975) exams. Data from a subsample of veterans who completed a military service interview during the sixth exam (1997–1999) also were used. In the first set of analyses, we compared veterans to civilians on three marital outcomes for ages 15–59: (1) likelihood of never marrying, (2) age at first marriage, and (3) likelihood of divorce. Next, we investigated the negative consequences of increasing combat exposure on the same marital outcomes. All analyses controlled for age in 1941 and occupation. Results: Overall, 88% of the sample remained in their first marriage with no differences between veterans and civilians. We found no effects of military service on the timing of first marriages on the likelihood of divorce during young and middle adulthood. However, among those who had not married before WW II, veterans were significantly more likely to remain unmarried compared with civilians; odds ratio = 1.52 (1.10, 2.09). The level of combat exposure did not predict any of the three marital outcomes among WW II veterans. In fact, none of the other military service characteristics assessed (i.e., age of military induction, years of service, and service-connected disability) predicted marital outcomes. We found that age at the beginning of WW II impacted the timing and stability of marriage in both veterans and civilians. Finally, we identified cultural effects on the likelihood of marriage between Nisei and Kibei groups with Nisei men being less likely to marry. Conclusion: Similar to other groups in this era, long-term marriage with one partner was the norm for both veterans and civilians. For a small portion of American men of Japanese descent, military service seemed to impact the transition into marriage. However, we found no differences in the timing of marriage or the likelihood of divorce based on military service or level of combat exposure. While our findings are inconsistent with previous research on the impact of military service and combat exposure, much of that research was conducted with mainland veterans, usually of European descent. There appears to be little long-term disruption of life course events. Results highlight the importance of studying diverse groups of veterans to understand how experiences in the military interact with pre-military factors in defining long-term responses to military service.